The dynamics of rural household expenditure in Indonesia - Junaedi Junaedi (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
Many indicators can be used to measure welfare, one of which is the proportion of food expenditure. This study aims to analyze and calculate the proportion of food expenditure in rural Indonesia and analyze the relationship between the proportion of food expenditure as an indicator of welfare. The method used is descriptive statistical analysis. The data used are national socio-economic survey data in 1996:2017. This paper shows that the pattern of household spending varies in income groups during the period analyzed. Likewise, the proportion of food expenditure varies depending on the income level; the higher the income level, the smaller the proportion of food expenditure.